The policies adopted by the international community to absorb refugees - Ben Wargla, Nadia (Journal of Humanities & Social Sciences, 2018)
It is crucial to point out to the refugee’s crisis worldwide. The refugee question should be raised and treated at an international level since it doesn’t only concern the hosting countries or the countries of origins, it has a considerable impact on the neighbouring states. The coming of the refugees to the developed and safe countries is not without a consequence, as they affect the hosting countries in so many ways. Furthermore, the alarming conditions of refugees worldwide lead to alarming health issues mainly affecting women and children. The refugee crisis needs effective solutions at a social, economic and political level within the hosting countries along with the countries of origins taking into consideration the human rights norms.
Keywords: refugee; refugee phenomenon; countries of asylum; displacement crisis; legal obligations; efforts of the international community; human rights